Observational study of central metastases following thyroid lobectomy without a completion thyroidectomy for papillary carcinoma - Cho, Jin Seong (The Korean Surgical Society, 2012)
PURPOSE: There are no guidelines for the optimal timing of the decision of when to perform completion thyroidectomy, and controversy exists regarding how the timing of completion thyroidectomy impacts survival patterns. We investigated the legitimacy of an observational strategy in central node metastasis after thyroid lobectomy for papillary thyroid cancer (PTC). METHODS: We retrospectively evaluated 522 consecutive patients who underwent thyroid lobectomy. Of the 69 patients with central metastasis, 61 patients (88.4%) were included in an observational study under cautious evaluation with informed consent by the patients, and compared with an observation arm of 180 postlobectomy N0 (node negative proven) patients. RESULTS: Of the 522 patients, six (1.1%) thyroid, five (0.9%) central, and two (0.4%) lateral recurrences were observed. Lateral recurrences occurred in the immediate completion N0 and Nx groups but not in the N1a observation arms. There were two (3.3%) central recurrences without thyroid or lateral recurrence on the observation arm of N1a observation patients. But two (1.1%) thyroid and three (1.7%) central recurrences were on the observation arm of N0 patients. In Kaplan-Meier survival curves for central or lateral recurrences between observation arms for the N1a and N0 groups, no significant difference was found between the N1a and N0 observation arms (P = 0.365). CONCLUSION: The timing of when to perform completion thyroidectomy in central metastases-proven patients after lobectomy for PTC should be based on the patient's risk category.